(untitled) (Epidemiology, Biostatistics, and Public Health, 2022)
Objectives The purposes of this study were to assess the prevalence of underweight, overweight, and obesity and to evaluate the nutritional habits, and related factors among the Students of Jazan University. Methods This cross-sectional study was carried out during the academic year 2014/2015 in Jazan University, Gizan, South West Saudi Arabia. A total of 436 students 19–25 y of age were examined. The questionnaires, including items on eating habits, lifestyle, and socio-demographic characteristics, were completed by the students. Data on weight, height were also collected. The data were analyzed using descriptive statistics and chi-square test. Differences were considered statistically significant at P. value < 0.05. Results The mean weight for males and females were 67.84 and 54.79 kg respectively, with significant differences between males and females (P. value <0.05). The mean BMI for all study participants was reported as 23.31 (kg/m²), also with significant difference between the males and females groups. About 45% of the students were of normal weight; the rate of obesity and underweight among students was very high (33.6% and 21.1% respectively), and their dietary habits were unhealthy. Regularity of meals was found only among (16.5% and 20.4%) males and females respectively. 83.3% of males and 95.1% of females reported eating snacks during the day. Conclusion The results of this study suggest that the prevalence of overweight and obesity were very high among the studied students. The study showed the need for health education programs on nutritional education in universities in order to increase awareness of students towards healthy eating and lifestyle.